Utilities of traditional and novel biomarkers in the management of acute kidney injury. (18th May 2020) - Chen, Li-Sheng; Singh, Ravinder J.
Abstract: Acute kidney injury (AKI), characterized by an abrupt decrease of renal function, is associated with multiple etiologies and pathological mechanisms. Clinically, AKI has traditionally been defined and stratified by rising serum creatinine and a decrease in urine output. However, neither criterion is sensitive enough for early detection of AKI, nor can they provide useful etiological information for making appropriate therapeutic decisions. Therefore, numerous AKI biomarkers have been discovered, investigated and tested in large cohort studies in the hope of improving diagnosis and clinical management of AKI. In this review, we describe in detail recent developments on three novel AKI markers: neutrophil gelatinase-associated lipocalin, liver-type fatty acid-binding protein, and the composite score of insulin-like growth factor-binding protein 7 and tissue inhibitor of metalloproteinase 2 ([TIMP-2][IGFBP7]). We also examine several emerging AKI markers, including proenkephalin A 119-159, fibroblast growth factor 23, calprotectin, and endocan that are in the pipeline for market approval. To date, the translation of new AKI biomarkers into clinical use has been limited. We discuss existing barriers and ongoing efforts to overcome the hurdles. Lastly, we propose several practical approaches, such as incorporating emerging markers into bundled care for AKI and conducting clinical validation studies in specific subpopulation (e.g. pediatric patients after cardiac surgery, adult major trauma patients) to avoid the confounding effects of other complications, as a focus for future research in marker-guided AKI patient management.